Accelerated Corneal Collagen Cross-Linking Using Topography-Guided UV-A Energy Emission: Preliminary Clinical and Morphological Outcomes - Cosimo Mazzotta; Antonio Moramarco; Claudio Traversi; Stefano Baiocchi; Alfonso Iovieno; Luigi Fontana (Journal of Ophthalmology)
Purpose. To assess the clinical and morphological outcomes of topography-guided accelerated corneal cross-linking. Design. Retrospective case series. Methods. 21 eyes of 20 patients with progressive keratoconus were enrolled. All patients underwent accelerated cross-linking using an ultraviolet-A (UVA) exposure with an energy release varying from 7.2 J/cm2 up to 15 J/cm2, according to the topographic corneal curvature. Uncorrected (UDVA) and corrected (CDVA) distance visual acuity, topography, in vivo confocal microscopy (IVCM), and anterior segment optic coherence tomography (AS-OCT) were evaluated preoperatively and at the 1, 3, 6, and 12 months postoperatively. Results. 12 months after surgery UDVA and CDVA did not significantly vary from preoperative values. The average topographic astigmatism decreased from -4.61±0.74 diopters (D) to -3.20±0.81 D and coma aberration improved from 0.95 ± 0.03 μm to 0.88 ± 0.04 μm after surgery. AS-OCT and IVCM documented differential effects on the treated areas using different energies doses. The depths of demarcation line and keratocyte apoptosis were assessed. Conclusions. Preliminary results show correspondence between the energy dose applied and the microstructural stromal changes induced by the cross-linking at various depths in different areas of treated cornea. One year after surgery a significant reduction in the topographic astigmatism and comatic aberration was detected. None of the patients developed significant complications.